Eastern European Jewish American narratives, 1890-1930 : struggles for recognition - Mihăilescu, Dana (Lexington studies in modern Jewish history, historiography, and memory, 2018)
This book offers a comparative study of the Jewish response to identity structures in Eastern Europe and the United States from 1890 to 1930 in narratives by immigrant writers from the Pale of Settlement and Romania.